Implementasi Moderasi Beragama Dan Implikasinya Terhadap Sikap Inklusif Di Paguyuban Ananda Tahun 2023/2024 - Reza Arya Pradana (Journal on Education, 2023)
Paguyuban Ananda is a Buddhist religious organization whose members come from various cross-border councils in Buddhism. The differences that exist require the right strategy to unite so that there is no conflict that can divide groups within one sphere of society. Steps that can be taken are to form an attitude of Religious Moderation. Religious moderation has an important role in forming an inclusive attitude between religious communities. Moderation is an attitude of understanding differences and eliminating extreme or excessive attitudes (Saifudin, 2019:15). Harmony and balance in social life is one of the efforts to strengthen religious moderation so that the implementation of religious moderation becomes the first step in creating an attitude of implication for Religious Communities (Religious Research and Development and Training Agency of the Ministry of Religion of the Republic of Indonesia, 2019: 120).The method used in this research is the qualitative phenomenological method, in phenomenological research there are main characteristics, namely (a) referring to reality, in this case awareness of a clear object, (b) understanding the meaning of events and their relationships to people who are in certain situations, (c) start with silence. Based on a phenomenological view, researchers try to understand the meaning of events and their relationships to ordinary people in certain situations. The use of a phenomenological approach is intended to describe symptoms or phenomena that appear as they really are, Moleong (2010: 8). Then the researcher collected data from each person, namely the three respondents who experienced the phenomenon, and developed a combined description of the essence of the experience for all individuals. The description developed consists of "what" the individual experiences and "how" the individual experiences it (Creswell, 2007: 58).The results of the research are in the form of information from all subjects through interviews. The researcher explained that there were several focus themes discussed, namely (1) Problems of Buddhists, (2) Causes of Problems (3) Religious Moderation (4) Benefits of Religious Moderation (5) Implementation of Religious Moderation (6) Attitudes of Religious Moderation in the Ananda Community (7 ) Implications in diversity.Based on the explanation above, it can be concluded that the implementation of religious moderation in the Ananda community has been implemented well. This can be seen from the problems of Buddhists which previously emerged and became obstacles in the activities of Buddhists which can be improved through a good understanding of religious moderation for Buddhists so that the implementation of religious moderation is able to form an inclusive or open attitude among Buddhists in the Ananda Community who have different Buddhist religious assembly backgrounds, become mutually accepting of diversity, openness in carrying out joint activities and able to resolve every problem through joint discussions and the erosion of fanatical attitudes in religious assemblies. Buddha in Kaloran sub-district, especially in the Ananda community.